Real-time monitoring of high-intensity focused ultrasound lesion formation using acousto-optic sensing. - Lai, P; McLaughlan, JR; Draudt, AB; Murray, T; Cleveland, R; Roy, R (2011)
High-intensity focused ultrasound (HIFU) is a promising modality that is used to noninvasively ablate soft tissue tumors. Nevertheless, real-time treatment monitoring with diagnostic ultrasound still poses a significant challenge since tissue necrosis, in the absence of cavitation or boiling, provides little acoustic contrast with normal tissue. In comparison, the optical properties of tissue are significantly altered accompanying lesion formation. A photorefractive crystal-based acousto-optic (AO) sensing system that uses a single HIFU transducer to simultaneously generate tissue necrosis and pump the AO interaction is used to monitor the real-time optical changes associated with thermal lesions induced in chicken breast ex vivo. It is found that the normalized change in AO response increases proportionally with the volume of necrosis. This study demonstrates AO sensing can identify the onset and growth of lesion formation in real time and, when used as feedback to guide exposures, results in more predictable lesion formation.